PERANAN GURU DALAM MENGGUNAKAN MEDIA GAMBAR UNTUK MENGEMBANGKAN KEMAMPUAN BERBAHASA ANAK DI TK NABILA MARAPALAM PADANG - Farlina, Reni - (Bimbingan dan Konseling, 2014)
This research background overshadow by fact of field in developing ability tell a story childof TK, teacher use various media in submitting story to child, like using break even picture mediaanimal, plant, environmental, and ownself. Target of this research is to know picture of (1) Role ofteacher in developing ability of child Ianguage picture media, (2) Role of teacher in developing abilitytell a story child media draw TK Nabila Marapalam Field. This researc descriptive approachqualitative that is depicting symptoms, and fact of realita exist in field are there him about role ofteacher in developing child Ianguage picture media. As for becoming research informan: Teacher ofB1, B2, pupil and kepsek of B2. Instrument which researcher use in this research interview andobservation, technique which used in data processing data discount, displayed data, withdrawal ofconclusion, improving authenticity of result, and narasi result of analysis. Result of research theobtained: (1) Role of teacher in developing ability tell a story child media draw that is ( a) child canrepeat teacher, ( b) child can tell a story about provided ganbar or which made self, (c) child interestwith given picture media teacher. (2) Role of teacher in developing ability enquire child media drawthat is: (a) in course of learning child will enquire simply, (a) child can question of teacher simply, (b)teacher of draw the picture less taken a fancy to child, (c) teacher will give reword to child which willtell a story and enquire to the fore, teacher will invite child play at game if child have started to tire of